Effect of cooling rate on the structure and electrochemical properties of Mn-based oxyfluorides with cation-disordered rock-salt structure - Kseniya V. Mishchenko; Maria A. Kirsanova; Arseny B. Slobodyuk; Anna A. Krinitsyna; Nina V. Kosova (Chimica Techno Acta)
According to the extensive studies in the field of high-energy cathode materials for lithium-ion batteries (LIBs), Mn-based oxyfluorides Li1.2Mn0.6+0.5yNb0.2–0.5yO2–yFy with Li-excess and cation-disordered rock-salt structure capable of reversible cationic and anionic redox reactions are among the most promising candidates. In this work, a series of Mn-based oxyfluorides with y = 0.05, 0.10, 0.15 were obtained using mechanochemically assisted solid-state synthesis with different cooling rates. Transmission electron microscopy, electron paramagnetic spectroscopy (EPR) and nuclear magnetic resonance spectroscopy (NMR) show that increasing the amount of fluorine promotes local ordering in crystals with the formation of isolated clusters of Mn3+–O2––Mn4+ that interrupt lithium diffusion. The occurrence of local ordering depends on the conditions of synthesis and affects electrochemistry. It was found that more clusters are formed in slowly cooled samples than in quenched ones. The best electrochemical characteristics with reversible capacity of 150 mAh·g–1 at room temperature were demonstrated by the Li1.2Mn0.65Nb0.15O0.90F0.10 sample obtained by quenching.